Polystyrene nanoparticles aggravate the adverse effects of di-(2-ethylhexyl) phthalate on different segments of intestine in mice. (October 2022) - Yu, Ziying; Xia, Yinyin; Cheng, Shuqun; Mao, Lejiao; Luo, Shiyue; Tang, Shixin; Sun, Wei; Jiang, Xuejun; Zou, Zhen; Chen, Chengzhi; Qiu, Jingfu; Zhou, Lixiao
Abstract: Emerging evidence indicates that nanoplastics (NPs) can transport organic pollutants such as di-(2-ethylhexyl) phthalate (DEHP) into organisms and induce adverse health effects. Nevertheless, the toxic effects of NPs combined with DEHP on mammalian intestine are still unclear. In this study, the C57BL6J mice were exposed to polystyrene nanoparticles (PSNPs), DEHP or them both for 30 days to determine their effects on different segments of intestine and the gut microbiota. As a result, DEHP alone or co-exposure to DEHP and PSNPs induced histological damages in all intestinal parts, mainly manifested as the decreased villus lengths, increased crypt depths in the duodenum, jejunum and ileum and decreased villus counts accompanied with decreased epithelial area in the colon. Moreover, decreased mucus coverage, down-regulated Muc2 expression levels as well as the broken tight junctions were observed in intestinal epithelium of mice, particularly obvious in the co-treatment groups. In general, as manifested by greater alterations in most of the parameters mentioned above, simultaneously exposed to PSNPs and DEHP seemed to induce enhanced toxic effects on intestine of mouse when compared with DEHP alone. Furthermore, the altered community composition of gut microbiota might at least partially contribute to these abnormalities. Overall, our results highlight the aggravated toxicity on different segments of intestine in mammalians due to co-exposure of PSNPs and DEHP, and these findings will provide valuable insights into the health risk of NPs and plastic additives. Graphical abstract: Image 1 Highlights: Oral exposure to DEHP but not low-dose PSNPs induced intestinal impairments in mouse. PSNPs aggravated the toxic effects on intestine of mouse induced by DEHP. The induced intestinal damages appeared to have no segment-specificity. The disturbed gut microbiota might contribute to such intestinal lesions.